Dichlorido(2-{ 3-(morpholin-4-ium-4-yl)propyl iminomethyl}phenolate)zinc - Hisham, N.A.I.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2011)
In the zwitterionic zinc title complex, [ZnCl2(C14H20N2O2)], the Zn-II ion is four-coordinated in a distorted tetrahedral geometry. The Schiff base ligand employs its phenolate O and imine N atoms to coordinate the metal atom in a bidentate mode. Two Cl atoms complete the tetrahedral coordination environment. In the crystal, a pair of N-H center dot center dot center dot O hydrogen bonds connect the molecules into a centrosymmetric dimer. C-H center dot center dot center dot O, C-H center dot center dot center dot Cl and C-H center dot center dot center dot pi interactions are also observed.